Clustering Indonesian Neobanking Users Through Extended UTAUT 3 for Retention Campaign Strategy - Rahmatulloh, Febriandi; Sumarwan, Ujang; Hartoyo, Hartoyo; Sartono, Bagus (ETIKONOMI, 2025)
Research Originality: This study develops a behavior-anchored segmentation framework for Indonesian neobank users by extending the Unified Theory of Acceptance and Use of Technology (UTAUT-3) with trust and marketplace application usage, providing deeper insights into user behavior. Research Objectives: The research aims to identify distinct neobank user segments and key behavioral drivers to support targeted strategies in digital financial services. Research Method: An extended UTAUT-3 model incorporating trust and marketplace usage was validated through Structural Equation Modeling (SEM). Balanced Iterative Reducing and Clustering using Hierarchies (BIRCH) clustering was applied to data from 386 active users, with segment validity confirmed using Elbow, Gap, and Silhouette methods. Empirical Results: The results revealed that trust, habit, and marketplace usage emerged as primary drivers of engagement and user recommendations. This study identifies four user segments: transitioning explorers, urban occasionalists, rural digital enthusiasts, and cost-conscious digital natives. Implications: Urban Occasionalists and Rural Digital Enthusiasts show strong potential for long-term growth. Targeted engagement and personalized retention strategies for these segments can enhance customer lifetime value and strengthen user advocacy. JEL Classification: G21, M31, C38